2019
DOI: 10.1002/anie.201904034
|View full text |Cite
|
Sign up to set email alerts
|

Development of Chemo‐ and Enantioselective Palladium‐Catalyzed Decarboxylative Asymmetric Allylic Alkylation of α‐Nitroesters

Abstract: We describe the development of aP d-catalyzed decarboxylative asymmetric allylic alkylation of a-nitro allyl esters to afforda cyclic tetrasubstituted nitroalkanes.O ptimization of the reaction parameters revealed unique ligand and solvent combinations crucial for achieving chemo-and enantioselective C-alkylation of electronically challenging benzylic nitronates and sterically encumbered 2-allyl esters.S ubstrates were efficiently accessed in acombinatorial fashion by across-Claisen/ a-arylation sequence.The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…More promising results were recently published by Trost and co-workers. After an initial study of the intermolecular Pd-catalyzed allylic alkylation of α-secondary benzylic nitroalkanes with allyl methyl carbonate, which afforded the desired C-allylated products, but only in moderate ee values, 632 they turned their attention to the corresponding decarboxylative variant. 633 They found that both the chiral ligand and the solvent had a significant effect on the ratio of C - versus O -allylation.…”
Section: Asymmetric Decarboxylative Allylic Substitutionmentioning
confidence: 99%
See 2 more Smart Citations
“…More promising results were recently published by Trost and co-workers. After an initial study of the intermolecular Pd-catalyzed allylic alkylation of α-secondary benzylic nitroalkanes with allyl methyl carbonate, which afforded the desired C-allylated products, but only in moderate ee values, 632 they turned their attention to the corresponding decarboxylative variant. 633 They found that both the chiral ligand and the solvent had a significant effect on the ratio of C - versus O -allylation.…”
Section: Asymmetric Decarboxylative Allylic Substitutionmentioning
confidence: 99%
“…A range of aromatic groups with differing electronic properties were tolerated, as were α-ethyl nitroesters and bulky β-siloxymethallyl esters, forming α-allylated benzylic nitro compounds in up to 99% yield and up to 98% ee . 632 …”
Section: Asymmetric Decarboxylative Allylic Substitutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scheme 3 Pd-catalyzed DAAA of 1,4-diazepan-5-ones A Pd-catalyzed DAAA pathway of allyl nitroesters have been developed by Trost group, furnishing acyclic asymmetric tetrasubstituted nitroalkanes via alkylation of sterically hindered π-allyl substrates (Scheme 4). 33 The reaction proceeded with L1 and Pd2dba3 as the catalyst in ethyl acetate to generate the alkylation products in up to 99% yield and 98% ee. Due to the competitive O-alkylation pathway during Pd-catalyzed DAAA reaction, combination of L1 and the solvent ethyl acetate is crucial for the C-alkylation pathway to give the desired products.…”
Section: Scheme 2 Generation Of Chiral Dihydroquinolinones Via Pd-catalyzed Daaa From δ-Valerolactamsmentioning
confidence: 99%
“…The palladium-catalyzed rearrangement of allyl enol carbonates is an efficient and versatile method to access stereochemically enriched α-allylated carbonyl containing compounds (see Scheme a) . In contrast to classical enolate alkylation chemistry, these reactions avoid the requirement of stoichiometric strong base, allowing for better functional group tolerance and high chemoselectivity and regioselectivity …”
mentioning
confidence: 99%